The Impact of Carbon Dioxide and Other Greenhouse Gases on Forest Ecosystems, IUFRO Series, No. 8. - Karnosky, David, 1949-; Ceulemans, R. J. M.; Scarascia-Mugnozza, G.; Innes, John L. (CAB International, 2001)
This book provides a review, written by international forest scientists, of what is known about the impact of elevated CO2 and other greenhouse gases, on forest ecosystems.